1970
DOI: 10.3329/jbs.v15i0.2202
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life Extension of Banana (<i>Musa sapientum</i>) by Gamma Radiation

Abstract: The effect of gamma radiation on the shelf life extension of Bananas was studied. Bananas were treated with three gamma radiation doses of 0.30k Gy; 0.40k Gy and 0.50k Gy for 5 mins respectively and stored in a dry place under room conditions (25±2°C/ 80± 5% RH). The physical conditions of the radiation treated and control bananas were observed at every 2 days interval for their organoleptic properties till spoilage. The control bananas ripened within 6 days while the gamma irradiated bananas ripened within 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
(4 reference statements)
5
6
0
Order By: Relevance
“…Ascorbic acid content decreased with the increase of dose and storage time but it was not significant difference among all samples at the same time. The result was similar with the results of Zaman, Paul, Alam, Ibrahim, & Hassan (2007) reported that ascorbic acid content of irradiated bananas at dose lower than one kGy was not significant difference among all samples. Zhang, Deng, Fu, & Weng (2014) reported the same results on ascorbic acid content of Shatang mandarin that was not significant difference among treated groups and the control until 30 d at 4 º C after using gamma irradiation and refrigerated storage.…”
Section: Results and Discussion A) Effect Of Electron Beam Irradiatiosupporting
confidence: 91%
“…Ascorbic acid content decreased with the increase of dose and storage time but it was not significant difference among all samples at the same time. The result was similar with the results of Zaman, Paul, Alam, Ibrahim, & Hassan (2007) reported that ascorbic acid content of irradiated bananas at dose lower than one kGy was not significant difference among all samples. Zhang, Deng, Fu, & Weng (2014) reported the same results on ascorbic acid content of Shatang mandarin that was not significant difference among treated groups and the control until 30 d at 4 º C after using gamma irradiation and refrigerated storage.…”
Section: Results and Discussion A) Effect Of Electron Beam Irradiatiosupporting
confidence: 91%
“…From the whole distribution of weight loss during storage, grapes irradiated at 0.2 kGy showed a slightly lower result from others (except grapes irradiated at 0.4 kGy on day 7), but there was no statistical difference. This result is in agreement with Zaman et al (2007) who found that there were no remarkable changes in the moisture contents of gamma irradiated bananas during the storage period. Whereas Al-Bachir (1999) reported that 'Baladi' grape irradiated at 0.5 kGy had weight loss higher than the control fruit after 4 weeks in storage period, but there was no difference in weight loss between control and irradiated 'Helwani' grape.…”
Section: Weight Losssupporting
confidence: 93%
“…Preserving fresh banana is quite challenging (Mohapatra et al, 2010 ). Various chemical and physical approaches are employed in the preservation of banana (Zaman et al, 2007 ; Kudachikar et al, 2011 ; Mohapatra et al, 2011 ). However, consumer inclination toward foods containing biopreservatives and less chemical preservatives triggered the search for natural products that can be used for biopreservation (Barbosa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%